Cinematographs contextualising historical, political and philosophical influences on the development of education in Vietnam - Mo, Seng-Yeuy (Alex) (Curtin University, 2003)
It is arguable that at all times the long-term prosperity of a nation is inextricably linked to its educational system, especially of higher education. This study of Vietnam's educational structure and system is both unique and necessary. It provides detailed information and considerable analysis not previously available to readers outside Vietnam. As a historical study, it covers aspects of more than 2,000 years of the country's educational developments, from the invasion of China in 111 B.C. to the present. The study is divided into six chapters, each of which deals with a major period of time. Each chapter is self-contained. Historical background and essential materials are presented and analysed. The writing of historical events is based on chronological order. Vietnam was a country without written language before the coming of the Chinese who, in their invasion of Vietnam in 111 B.C., brought with them their civilization, culture, educational system and language. The introduction of Chinese language to Vietnam can be taken as the overture of Vietnamese education. The first two chapters provide detailed information and historical factors as to how an early educational system of Vietnam was established under the influence of China and through its impact of education on the formation of a Confucian political system and Confucian society, which continued to exist for over 2,000 years. The political decline of China in the late 19th century provided the opportunity for the French to enter Vietnam and finally replace the Chinese sovereignty over the country in 1885. The invasion and ruling of the French (1886-1954) brought forward significant changes in Vietnam politically, socially and educationally.The French introduced a new, modem educational system to Vietnam and set up an elite colonial educational system which had a great impact on Vietnamese society as well as its education. Traditional Chinese education and its imperial examination system commenced to fade out in Vietnam from the early 20th century and came to an end in 1917. During this colonial period, Western ways of thinking and culture began to flow into Vietnam and continued thenceforth. With the division of the country into North and South as separate regimes under the Geneva Accords in 1954, the educational systems of each regime developed under different political systems and different ideologies from 1955-1975. In the North, the educational system was totally reformed according to Communist doctrine while in the South, education continued to develop in the Western ways. The world-known Vietnam War ended in April 1975. However, the unification of the North and South failed to be effected in many aspects due to varied ideologies and political systems. During the period of 1975-85 Vietnam underwent a transitional reform of education in the South, which continued up to the practice of the nation's `open-door policy' starting from 1987. Narration of a significant profile of attributes of Vietnam's system of education today is fully sketched. The concluding chapter comprises two major parts; the summing up and a general review on Vietnam's educational system and practices, together with some of the issues evident in the system at present.